Monitoring of radionuclides in water for human consumption in the county of Angra dos Reis - Mariana Ferreira Gonçalves; Ana Cristina de Melo Ferreira; Adriana Belmiro de Oliveira; Julio Cesar Toledo de Almeida; Marise Paulina da Silva Alves Cunha (Brazilian Journal of Radiation Sciences)
The radiological impact for members of the population living in Angra dos Reis- RJ was assessed using environmental monitoring data from radium, lead, uranium, thorium and cesium in water for human consumption. For this, were collected and analyzed by radiometry (134Cs and 137Cs), radiochemical (226Ra, 228Ra and 210Pb) and mass spectrometry with inductively coupled plasma (238U and 232Th). From the results, it was observed that the concentrations found were lower than the values established by CONAMA, WHO and the Ministry of Health. It was concluded that the presence of these radionuclides in the collected waters is natural and with levels that are not harmful to health.